POSTPARTUM EXPERIENCE IN YOUNG MOTHERS - Trisetyaningsih, Anugerah Destia; Rokhanawati, Dewi; Ernawati, Dwi (Jurnal Kesehatan - STIKes Prima Nusantara, 2021)
Introduction: The puerperium or postpartum period is considered a vulnerable time for mothers, especially new mothers or young mothers, because they are simultaneously faced with the demands of caring for their babies and experience the physical, emotional, and social changes that occur.Objective: This study aims to determine the experience of childbirth in young mothers.Method: The subjects in this scoping review were young mothers in the postpartum period. The method used was adapted from Askey and O'Malley with 5 stages: identifying the scoping review question, identifying relevant articles, selecting articles, data charting, result in data presentation, discussion, and conclusion. Search for relevant articles through 4 databases, namely PubMed, ScienceDirect, Wiley, and Grey Literature through Google Scholar, published from 2009-2019. This study is qualitative research.Results: The results after selecting articles obtained 7 relevant articles and obtained 3 themes that emerged, namely obstacles (both from meeting nutritional needs, physical changes, and baby care, family planning, economy and stigma), the support needed (from partners, families and health workers), and the psychology of young mothers during the postpartum period, psychology positive (happy, ready to become mothers) and negative (anxiety, sadness, unpreparedness and emotional instability)Conclusion: Young mothers in the postpartum period need high social support to physically, psychologically, and socially prepare mothers. There is a need for more in-depth research regarding the conditions and psychology of young mothers in this period to provide recommendations for improving the health and well-being of young mothers and babies.